Protocol Adherence in Managing Diabetic Macular Edema at Eye Center in Surabaya - Tedjaprasadja, Leonardo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Diabetes is one of burden disease worldwide due to its complications. Microvascular complications can be manifested in sight threatening conditions such as Diabetic Macular Edema. Treatments for Diabetic Macular Edema are varied which can be done by pan-retinal coagulation laser, done with intravitreal injection of anti-vascular endothelial growth factor (anti VEGF) or intravitreal injection of corticosteroid. There are many treatment protocols available according to American Academy of Ophthalmology such as Protocol I while in Indonesia intravitreal injection of anti VEGF is used as first line. This study uses descriptive method and quantitative data to show the treatment adherence to the available protocol. This study provides a descriptive overview of treatment patterns for diabetic macular edema (DME) at an eye center in Surabaya between January and December 2021. Among the 88 respondents who met the inclusion criteria, the majority (59.1%) received intravitreal corticosteroid injections, while 40.9% were treated with intravitreal anti-VEGF agents. The largest proportion of respondents was aged 60–69 years (36.4%), and male patients predominated overall (62.5%). In the anti-VEGF group, men constituted 56% of respondents, whereas in the corticosteroid group, men comprised 71%. In light of the findings, it is recommended that clinical practice at the study site be further aligned with evidence-based guidelines, particularly the American Academy of Ophthalmology (AAO) and Indonesian Society of Ophthalmologists (PERDAMI) protocols, which advocate intravitreal anti-VEGF agents as the first-line therapy for DME with visual impairment. Strengthening physician awareness of guideline-concordant care, improving patient access to anti-VEGF therapy, and addressing potential barriers such as cost and availability may help optimize treatment outcomes.